Perlindungan Perempuan dalam Hukum Islam di Indonesia (Analisis terhadap Hukum Perkawinan dan Kewarisan) - Abdul Jamil (Fakultas Hukum Universitas Islam Indonesia, 2003)
In comprehending the quranic text and Hadits (prophet tradition) systematically. The position of women on marriage and legacy is getting sub-ordination. The men is positioned and symbolized as a superior because of his obligation and responsibility isconsidered bigger than the women. Recently, through contextual interpretation ongender justice dimension, treatment and placement of women position proportionally and parallelly with the men have become the frame and innovation paradigm of Islamic Law for the two fields. Through this innovation the discriminative treatment and the view of the unsuitable cultural construction for the women is expected to be corrected and open our eyes for the justice in which recently they are closed by the misled cultural symbol.